2008
DOI: 10.2146/ajhp070582
|View full text |Cite
|
Sign up to set email alerts
|

Unlabeled uses of intravenous immune globulin

Abstract: A literature review identified more than 150 unlabeled uses of IVIG. The evidence for these uses is being interpreted in different ways by various reviewing organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 25 publications
(28 reference statements)
1
64
0
3
Order By: Relevance
“…Of these, only 97 have been reviewed by expert consensus, leaving the burden on the health plan to research available medical evidence for the remaining indications-a time-consuming process with the potential for inconsistent interpretation. 4 We found that only a small percentage of total requests were for indications with a current lack of consensus. An unexpected outcome was the high percentage of these cases that ultimately were authorized.…”
Section: ■■ Conclusionmentioning
confidence: 80%
See 1 more Smart Citation
“…Of these, only 97 have been reviewed by expert consensus, leaving the burden on the health plan to research available medical evidence for the remaining indications-a time-consuming process with the potential for inconsistent interpretation. 4 We found that only a small percentage of total requests were for indications with a current lack of consensus. An unexpected outcome was the high percentage of these cases that ultimately were authorized.…”
Section: ■■ Conclusionmentioning
confidence: 80%
“…5 In a separate study, Leong et al (2008) determined that interpretation of the medical evidence for Ig therapy among several types of organizations is inconsistent. 4 The goal of our analysis was to characterize the indications for which Ig is currently being requested and to look at other factors, including patient demographics, supporting evidence, and benefit coverage outcomes, to enhance the body of knowledge surrounding this therapy. The PA process used by health plans provides a dataset uniquely suited to capturing this information, whereas a retrospective claims analysis would not have captured requests denied by the health plans.…”
Section: Design Of Reviewmentioning
confidence: 99%
“…Off-label indications include several hematological, neurological, autoimmune and other disorders like multiple sclerosis, graft-versus-host disease in transplant patients, and prevention of antiphospholipid syndrome in miscarriage, severe asthma, Guillain-Barré syndrome, and progression of human immunodeficiency virus after delivery 5 . Mechanism of action is either as a substitute of missing antibodies at replacement doses (200-400 mg/kg/month) in the treatment of primary and secondary antibody deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose IVIG, 0.2 to 0.6 g/kg, has been used safely for the treatment of these disorders (1). IVIG is now used in higher immunomodulatory doses for the treatment of various autoimmune, inflammatory, and infectious diseases (2)(3)(4). For transplant recipients, IVIG has become the mainstay of therapy to desensitize highly HLA-sensitized patients and to treat antibody mediated rejection (AMR).…”
mentioning
confidence: 99%